The African Christian Diaspora: New Currents and Emerging Trends in World Christianity - Adogame, Afeosemime U. (Bloomsbury, 2013)
The last three decades have witnessed a rapid proliferation of African Christian communities, particularly in Europe and North American diaspora, thus resulting in the remapping of old religious landscapes. This migratory trend and development bring to the fore the crucial role, functions and import of religious symbolic systems in new geo-cultural contexts. The trans-national linkages between African-led churches in the countries of origin (Africa) and the "host" societies are assuming increasing importance for African immigrants. The links and networks that are established and maintained between these contexts are of immense religious, cultural, economic, political and social importance. This suggests how African Christianities can be understood within processes of religious transnationalism and African modernity.Based on extensive religious ethnography undertaken by the author among African Christian communities in Europe, the USA and Africa in the last 17 years, this book maps and describes the incipience and consolidation of new brands of African Christianities in diaspora. The book demonstrates how African Christianities are negotiating and assimilating notions of the global while maintaining their local identities.
Paid
Keywords: Religion / Christianity / General